2005
DOI: 10.1074/jbc.m412592200
|View full text |Cite
|
Sign up to set email alerts
|

N-cadherin Mediates Endocytosis of Candida albicans by Endothelial Cells

Abstract: Candida albicans is the most common cause of fungal bloodstream infections. To invade the deep tissues, blood-borne organisms must cross the endothelial cell lining of the vasculature. We have found previously that C. albicans hyphae, but not blastospores, invade endothelial cells in vitro by inducing their own endocytosis. Therefore, we set out to identify the endothelial cell receptor that mediates the endocytosis of C. albicans. We determined that endocytosis of C. albicans was not mediated by bridging mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 43 publications
2
108
0
Order By: Relevance
“…These results were concordant with our prior findings that adhesion and invasion of R. oryzae to host cells are independent processes mediated by different receptors (15). The independence of adhesion and invasion processes has been also reported for Candida albicans (26). The probable explanation for the adhesion function of CotH proteins when expressed in S. cerevisiae is that although CotH can mediate both adherence and invasion, in R. oryzae, other adhesins likely exist and can compensate for the loss of CotH function.…”
Section: Figuresupporting
confidence: 83%
See 1 more Smart Citation
“…These results were concordant with our prior findings that adhesion and invasion of R. oryzae to host cells are independent processes mediated by different receptors (15). The independence of adhesion and invasion processes has been also reported for Candida albicans (26). The probable explanation for the adhesion function of CotH proteins when expressed in S. cerevisiae is that although CotH can mediate both adherence and invasion, in R. oryzae, other adhesins likely exist and can compensate for the loss of CotH function.…”
Section: Figuresupporting
confidence: 83%
“…We used a modification of our previously described method (15,26). Confluent endothelial cells on a 12-mm-diameter glass coverslip were infected with 10 5 /ml RPMI 1640 medium R. oryzae cells that had pregerminated for 1 hour.…”
Section: Figurementioning
confidence: 99%
“…Epithelial cell membrane proteins that bound to C. albicans or S. cerevisiae were isolated and affinity-purified as previously outlined (5,(28)(29)(30). Proteins eluted from the fungi were separated by SDS/PAGE and detected by immunoblotting with antibodies against biotin (clone BN-32; Sigma-Aldrich), EGFR (sc-03; Santa Cruz Biotechnology), and HER2 (clone 3B5; Santa Cruz Biotechnology).…”
Section: Methodsmentioning
confidence: 99%
“…Confocal Microscopy. The accumulation of epithelial cell EGFR, HER2, and Ecadherin around C. albicans hyphae was visualized using a minor modification of our previously described methods (5,29). OKF6/TERT-2 cells were infected with 2 × 10 5 hyphae of the various C. albicans strains.…”
Section: Methodsmentioning
confidence: 99%
“…50 New research has found that N-cadherin expressed on the endothelium binds to C. albicans Als3 and Ssa1 in a complex that also contains an intracellular GTP-binding protein, septin-7. 87,88 This binding process induces endothelial cell microfilaments, thereby producing pseudopods that engulf the organism.…”
Section: Endothelial Cellsmentioning
confidence: 99%